Boosting the alkali metal ions storage performance of layered Nb2C with a molecular welding strategy. (1st December 2022) - Liu, Maocheng; Zhang, Dongting; Liu, Bao; Tian, Chenyang; Zhao, Bei; Wang, Yaqin; Wang, Yuanyi; Hu, Yuxia; Kong, Lingbin; Luo, Dan; Chen, Zhongwei
Abstract: MXenes are promising 2D-layered anode materials for rechargeable batteries. However, MXenes suffer from severe volume expansion and sluggish ion diffusion kinetics during ions insertion/extraction, leading to inferior battery performance. Herein, we developed a molecular welding strategy to stabilize layered structure and enlarge interlayer spacing of Nb2 C through a dehydration condensation reaction between the -COOH groups in 1, 3, 5-benzenetricarboxylic acid (BTC) molecules and -NH2 groups on the surface of the amino-functionalized Nb2 C, which enable the BTC to chemically weld into interlayers of Nb2 C (named as Nb2 C/BTC). The intercalation of BTC into Nb2 C contributes both pillar and strain effects to the 2D-layered Nb2 C, rendering its maximum utilization. Such Nb2 C/BTC with enlarged interlayer spacing and inhibited volume variation could remarkably promote the rate capability and cycling stability of Nb2 C when used as the electrodes of alkali metal ions batteries. A decent Li + /Na + ions storage capacity-retention of 86.6% (0.1 A g −1 )/93.5% (1.0 A g −1 ) can be presented. A much reduced ion diffusion barrier of 0.88 eV is also delivered in Nb2 C/BTC through DFT theoretical calculations. This work provides a new strategy for broadening the interlayer spacing and inhibiting the severe volume variation of MXenes for enhanced alkali metal ions storage. Graphical Abstract: A novel molecular welding strategy was proposed to broaden the interlayer spacing and simultaneously achieve the excellent structure stability of Nb2 C MXene, which exhibits superior rate capability and extraordinary cycle stability for alkaline metal ions storage. ga1 Highlights: A molecular welding strategy is proposed to broaden the interlayer spacing and guarantee structural durability of Nb2 C. The 2D layered Nb2 C/BTC exhibits enhanced specific capacity, rate capability and cycling stability for Li + /Na + storage. Theoretical calculation proves that expanded interlayer spacing reduces migration barrier and improve diffusion kinetics.